Educación superior inclusiva para las personas con discapacidad (2018)
The purpose of this article is to offer an overview of the existing regulations in higher education regarding the inclusion of people with disabilities in Colombia. Theme addressed in the research framework Development of tools to facilitate communication, learning and inclusion of people with disabilities, from features of the socio-critical paradigm that poses spaces for reflection on the levels of society, including their practices, beliefs and ways of operating, allowing them to be re-evaluated, improved and transformed in the community in general, becoming corresponding analysis between the theories that underlie the study and the practice that allows understanding the reality and transformation (Alvarado & García, 2008). To develop it, a tour through the international standards on inclusive education at the higher educational level, then outlines the regulations in the national context, beginning with the inclusion in basic education as a starting point for the discussion, is conclude by relating this with the challenges in higher education to ensure the inclusion of people with disabilities.